Вычислить производные: 1 ) y= корень из x^2-4/x^3 2)y= ln корень из x^2+4 3)y= sin^2(3x+2)/tgx^2
Вычислить производные: 1 ) y= корень из x^2-4/x^3 2)y= ln корень из x^2+4 3)y= sin^2(3x+2)/tgx^2
Ответ(ы) на вопрос:
[latex]y'=\frac{\sqrt{x^2-4}}{x^3}=\frac{(\sqrt{x^2-4})'*x^3-(\sqrt{x^2-4})*(x^3)'}{(x^3)^2}=\\=\frac{\frac{1}{2\sqrt{x^2-4}}*(x^2-4)'*x^3-\sqrt{x^2-4}*3x^2}{x^6}=\frac{\frac{2x}{2\sqrt{x^2-4}}*x^3-3x^2-\sqrt{x^2-4}}{x^6}[/latex] [latex]y'=(ln\sqrt{x^2+4})'=\frac{1}{\sqrt{x^2+4}}*(\sqrt{x^2+4})'=\\=\frac{1}{\sqrt{x^2+4}}*\frac{1}{2\sqrt{x^2+4}}*(x^2+4)'=\frac{2x}{2\sqrt{x^2+4}*\sqrt{x^2+4}}[/latex] [latex]y'=(\frac{sin^2(3x+2)}{tgx^2})'=\frac{(sin^2x(3x+2))'(tgx^2)-(sin^2(3x+2))(tgx^2)'}{(tgx^2)^2}=\\=\frac{2sinx(3x+2)*(sin(3x+2))'*tgx^2-sin^2(3x+2)*\frac{1}{cos^2x^2}*(x^2)'}{tg^2x^2}=\\=\frac{2sin(3x+2)*cos(3x+2)*(3x+2)'*tgx^2-\frac{2x*sin^2(3x+2)}{cos^2x}}{tg^2x^2}=\\=\frac{2sin(3x+2)*cos(3x+2)*3*tgx^2-\frac{2x*sin^2(3x+2)}{cos^2x}}{tg^2x^2}[/latex]
Не нашли ответ?
Похожие вопросы